Feasibility of N2 Binding and Reduction to Ammonia on Fe‐Deposited MoS2 2D Sheets: A DFT Study. Issue 34 (19th May 2017) - Azofra, Luis Miguel; Sun, Chenghua; Cavallo, Luigi; MacFarlane, Douglas R.
Abstract: Based on the structure of the nitrogenase FeMo cofactor (FeMoco), it is reported that Fe deposited on MoS2 2D sheets exhibits high selectivity towards the spontaneous fixation of N2 against chemisorption of CO2 and H2 O. DFT predictions also indicate the ability of this material to convert N2 into NH3 with a maximum energy input of 1.02 eV as an activation barrier for the first proton–electron pair transfer. Abstract : Bosch–Haber alternative? Mild conditions for N2 capture and catalytic conversion into NH3 is a key priority for "green fuels" technology. DFT findings show that Fe deposited on MoS2 2D sheets selectively captures N2 gas and converts N2 into NH3 with a maximum energy input of 1.02 eV, which arises from the activation barrier for the first H + /e − pair transfer.